2011
DOI: 10.7205/milmed-d-10-00377
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Chronic Obstructive Pulmonary Disease Among Veterans in the Urban Midwest

Abstract: Although chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality within the Veterans Health care Administration, its prevalence and recognition are not known. We measured airflow limitation and diagnosed COPD at the Cincinnati Veteran's Administration Medical Center. Participants were 326 outpatients who performed spirometry and completed questionnaires. Health care-provider-diagnosis and self-diagnosis of COPD were compared with COPD defined by forced expiratory volume in 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…This estimated prevalence of diagnosed COPD compares well with the 8.2% prevalence rate among Veterans in the southeastern US (Veterans Integrated Service Network 16) calculated by Sharafkhaneh and colleagues [26] and the 9.40% prevalence of diagnosed COPD within the VHA nationally in 1999 estimated by Yu and coworkers [27]. Previously, we demonstrated that the prevalence of measured airflow limitation was significantly greater than the prevalence of diagnosed COPD and that two thirds of Veterans with airflow limitation did not have a diagnosis of COPD [1]. Assuming that only one third of patients with COPD are diagnosed, the prevalence of diagnosed Veterans with COPD, 9.3%, is comparable to our previously measured 43% prevalence of airflow limitation using a threshold of FEV 1 /FVC < 0.7.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This estimated prevalence of diagnosed COPD compares well with the 8.2% prevalence rate among Veterans in the southeastern US (Veterans Integrated Service Network 16) calculated by Sharafkhaneh and colleagues [26] and the 9.40% prevalence of diagnosed COPD within the VHA nationally in 1999 estimated by Yu and coworkers [27]. Previously, we demonstrated that the prevalence of measured airflow limitation was significantly greater than the prevalence of diagnosed COPD and that two thirds of Veterans with airflow limitation did not have a diagnosis of COPD [1]. Assuming that only one third of patients with COPD are diagnosed, the prevalence of diagnosed Veterans with COPD, 9.3%, is comparable to our previously measured 43% prevalence of airflow limitation using a threshold of FEV 1 /FVC < 0.7.…”
Section: Discussionmentioning
confidence: 97%
“…At the Cincinnati Veteran’s Administration Medical Center (VAMC), the prevalence of airflow limitation is estimated to be 33-43% and COPD is significantly under-diagnosed and misdiagnosed [1]. In a 1996–2001 utilization review, 19% of men and 17% of women who received care from the Veterans Healthcare Administration (VHA) were diagnosed with COPD and COPD was the fourth most common discharge diagnosis at VHA hospitals [2].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of AFL at the Cincinnati VAMC is much higher than the general population and approximately two thirds of affected patients are not diagnosed with COPD. The prevalence of AFL at the Cincinnati VAMC is much higher than the general population and approximately two thirds of those affected patients are not diagnosed with COPD 10. All of our patients with AFL by LLN also met FR criteria and nine (20%) patients had COPD by FR alone.…”
Section: Discussionmentioning
confidence: 70%
“…Patients were recruited in random, chronological order and spirometry was performed according to the 1994 American Thoracic Society guidelines 21. Each participant completed a questionnaire about smoking habits, occupational exposures, respiratory diagnoses, and symptoms 10. AFL was defined by either fixed ratio (FR), the ratio of FEV 1 to the forced vital capacity (FVC), <0.70 or lower limit of normal (LLN), FEV 1 /FVC < LLN as determined by NHANES III 22.…”
Section: Methodsmentioning
confidence: 99%
“…2 At the Cincinnati Veterans Affairs Medical Center (VAMC), between 33–43% of patients have airflow limitation and COPD is significantly misdiagnosed and under-diagnosed. 3 In 2008, over 3200 Veterans received care for COPD at the Cincinnati VAMC, the top 20% of whom (ranked by COPD-related healthcare cost) accounted for all hospitalizations and Emergency Department (ED) visits, 90% of the expenditures, 60–70% of all encounters, and nearly 10% of the total operating budget for the hospital. 4 …”
Section: Introductionmentioning
confidence: 99%